Juridical Study of Customary Law In The Indonesian National Legal System - Setiawan, Irgi; Muzaffar Wahyu, Ariq; Rahman, Alip; Sutrisno, Anom (Asian Journal of Social and Humanities, 2024)
Customary law, as an integral part of the cultural and social identity of Indonesian society, has an important role in shaping the norms and values that prevail in various communities. This study aims to examine the juridical aspects of the recognition and application of customary law within the national legal framework, focusing on the constitution, laws, and regulations governing customary law. The research method used is the normative juridical method with an analytical-descriptive approach. The data analysed consisted of primary legal sources, such as the 1945 Constitution, laws, and court decisions, as well as secondary legal sources, including legal literature and previous research. The results show that although customary law is constitutionally recognised, there are significant challenges in its implementation at the national level. This is mainly due to the existence of legal dualism, norm conflicts between customary law and national law, and the lack of harmonisation in legislation governing the existence of customary law. The study concludes that further efforts are needed to harmonise customary law with national law through legislative reform, legal education, and public awareness raising. Thus, customary law can function effectively and fairly in the national legal system, while preserving Indonesia's cultural diversity.